2021
DOI: 10.1287/mnsc.2020.3870
|View full text |Cite
|
Sign up to set email alerts
|

The Reference Effect of Delay Announcements: A Field Experiment

Abstract: We explore whether customers are loss averse in time and how delay information may impact such reference-dependent behavior using observational and field experiment data from two call centers of an Israeli bank. We consider settings with no announcements and announcements of different accuracy levels. We face two key challenges: (1) we do not observe the reference points customers use in our data, as any other field studies, and (2) it is difficult to separate the reference-dependent behavior from the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…When customers are reassigned to a less‐favorable option with potential longer waiting, they would suffer loss and intensified disutility due to the tendency of loss aversion that discourages them from showing up. In fact, research that studies queue abandonment has shown that customers (patients) who have waited beyond the informed waiting time in the delay announcement at call centers (Webb et al., 2020, Yu et al., 2021) or at the emergency departments in hospitals (Luo et al., 2022), are more likely to abandon the service system. Our finding implies that the waiting time of a preferred option could also exhibit an important reference effect in shaping customer's no‐show behavior.…”
Section: Resultsmentioning
confidence: 99%
“…When customers are reassigned to a less‐favorable option with potential longer waiting, they would suffer loss and intensified disutility due to the tendency of loss aversion that discourages them from showing up. In fact, research that studies queue abandonment has shown that customers (patients) who have waited beyond the informed waiting time in the delay announcement at call centers (Webb et al., 2020, Yu et al., 2021) or at the emergency departments in hospitals (Luo et al., 2022), are more likely to abandon the service system. Our finding implies that the waiting time of a preferred option could also exhibit an important reference effect in shaping customer's no‐show behavior.…”
Section: Resultsmentioning
confidence: 99%
“…(2018), Whitt (1999), and Yu et al. (2016, 2017, 2021). We further refer interested readers to two survey books, Hassin and Haviv (2003) and Hassin (2016), and survey papers by Aksin et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Let 𝒰 𝖡 denote the set of all functions 𝜇(⋅) that satisfy the above assumptions. A commonly used example for 𝜇(⋅) is the piecewise linear utility model (Ho & Zheng, 2004;Yu et al, 2021):…”
Section: Production and Operations Managementmentioning
confidence: 99%